2023
DOI: 10.3389/fcimb.2023.1145950
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of fecal microbiota in cervical cancer patients associated with tumor stage and prognosis

Abstract: Cervical cancer (CC) is the fourth most frequent malignancy among women worldwide, and its prevention and treatment are evolving rapidly. The gut microbiota has been reported to play a crucial role both in the preservation of homeostasis and the development of cervical cancer. In this study, we collected fecal samples to investigate the microbial signatures in cervical cancer patients compared with healthy controls using 16S rRNA sequencing analysis and metagenomic next-generation sequencing (mNGS) testing. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…24,25 In cervical cancer patients, Ruminococcus decreases with increasing stages of the disease. 26 Variations with Pelvic RT On the one hand, the pre-RT composition of intestinal bacteria determines the incidence of post-RT diarrhea. In contrast, the composition of intestinal bacteria changes significantly during and post-RT, which also correlates with the incidence of diarrhea.…”
Section: Variation As Per Cancer Subtypementioning
confidence: 99%
See 1 more Smart Citation
“…24,25 In cervical cancer patients, Ruminococcus decreases with increasing stages of the disease. 26 Variations with Pelvic RT On the one hand, the pre-RT composition of intestinal bacteria determines the incidence of post-RT diarrhea. In contrast, the composition of intestinal bacteria changes significantly during and post-RT, which also correlates with the incidence of diarrhea.…”
Section: Variation As Per Cancer Subtypementioning
confidence: 99%
“…Erysipelotrichaceae belonging to Firmicutes phylum is also increased in colorectal cancer 24,25 . In cervical cancer patients, Ruminococcus decreases with increasing stages of the disease 26 …”
Section: Variations In Gut Microbiota In Health and Cancermentioning
confidence: 99%
“…The patient group exhibited a higher abundance of Prevotella , Porphyromonas , and Dialister , while the control group showed a higher abundance of Bacteroides , Alistipes , and members of the Lachnospiracea family[ 43 ]. Additionally, Chang et al [ 44 ] conducted an enrichment analysis of gut microbiota from patients with cervical cancer patients and healthy controls and found that the functions of the differentially expressed genes in the two groups, primarily associated with REDOX reactions, biosynthesis of other secondary metabolites, and amino acid transport and metabolism.…”
Section: Changes Of Gut Microbiota In Patientsmentioning
confidence: 99%
“…The reduction in these bacteria may impact overall intestinal health, thereby influencing vaginal health. Chang et al identified Ruminococcus 2 as a gut flora family closely linked to CC, suggesting its potential as a biomarker for predicting cervical cancer development [61]. Firmicutes, particularly Ruminococcus, plays a crucial role in polysaccharide degradation and contributes to human metabolism by converting cellulose into host nutrients [62].…”
Section: Microbial Influence On Cervical Cancer Development: Immune R...mentioning
confidence: 99%